Gaffe/Stutter - Trettien, Whitney Anne (punctum books, 2013)
Gaffe/Stutter is a dead letter to Deleuze's Logic of Sense. It began as a series of diagrams, two-dimensional memory palaces that sketch the vectors of each chapter's paradox; it became an elaborate plan for a web-based diagrammatic (r)e(n)dition of Logic of Sense, built on zoomable, annotatable high-resolution scans of these diagrams. Conceived as an anti-book - a visual reading schematic - this project eschews the line of text in favor of regimented grids, the ink-soaked grain of the remediated pen over the laser-burned face of print; playful reaction rather than academic protraction. This is not an analogy, or a product of the imagination, Gilles Deleuze and Felix Guattari would write in A Thousand Plateaus, but a composition of speeds and affects on the plane of consistency: a plan(e), a program, or rather a diagram, a problem, a question-machine. It ended as a directory of inert jQuery demos and digital scans: an image of Trafalgar Square at dusk, annotated with the words "Flag," "Small people on the steps," "A Statue," and "National Gallery Dome"; an empty html file titled 'delete.html'. The visitor who may happen to wander onto the website where these project demos are stashed would find herself stuck on Deleuze's definition of a paradox as initially that which destroys good sense as the only direction of becoming, but also that which destroys common sense as the assignation of fixed identities. From a series of diagrams to a dead-end digital directory, Gaffe/Stutter re-interprets a book that itself resists scholarly annotation. As with sense, it subsists in language; but it happens to things.